Porous SiC-mullite ceramics with high flexural strength and gas permeability prepared from photovoltaic silicon waste. Issue 1 (January 2020) - Xing, Zhiheng; Hu, Yuhang; Xiang, Daoping; Ma, Yanping
Abstract: In this paper, porous SiC-mullite ceramics (PSMCs) with high flexural strength and gas permeability were prepared with various mass fractions of MoO3 and Al2 O3 . Higher performance was achieved at low sintering temperatures and the problem of large amounts of cristobalite phase in the PSMCs was solved. The results show that 4 wt% MoO3 is optimal for the growth of mullite rods at a sintering temperature of 850 °C. Porosity was effectively controlled by the formation of interlocking structure and mechanical strength was not obviously affected. Therefore, the optimal content of Al2 O3 was 25 wt% in samples prepared at 850–1200 °C, as the flexural strength was generally higher than that in samples with other Al2 O3 contents. The highest flexural strength of 66.02 MPa was achieved at an open porosity of 45.4%, gas permeability of 2.32 × 10 −13  m 2, and permeance of 4.62 × 10 −5  mol m −2  s −1 Pa −1 in samples sintered at 1000 °C. This work is of significance for the industrial preparation of PSMCs from photovoltaic silicon waste.